Pengembangan Penyesuaian Sosial Mahasiswa melalui Bimbingan Pribadi dan Sosial - Pertiwi, Feby Nur; Sugandhi, Nani M; Hafina, Anne (Psikopedagogia, 2017)
The study aims to find out the improvement of social adjustment in university on International Studies on Science Education (IPSE) student of Universitas Pendidikan Indonesia (UPI) after being given social personal guidance. This study uses a quantitative approach to the type of experimental research. Subjects in this study were 44 students taken with random sampling technique. The data collection tool in this study used a scale of social adjustment in college. The data analysis in this study uses t-test. The results showed that personal social guidance can improve social adjustment in college students by using sociodrama, simulation, and experience techniques. This study presents an alternative strategy for academic advisors in universities to facilitate students in developing social adjustment skills in universities.